Bis(4-nitroanilines) in interactions through a π-conjugated bridge: conformational effects and potential molecular switches. (18th September 2017) - Guerrero, Tomás; Santillan, Rosa; García-Ortega, Héctor; Morales-Saavedra, Omar G.; Farfán, Norberto; Lacroix, Pascal G.
Abstract : DFT computation suggests that two dipolar chromophores in rotation around an organic bridge could be aligned by an electric field. Abstract : Two molecules, 2, 2′-(1, 4-phenylenebis(ethyne-2, 1-diyl))bis(4-nitroaniline) (PNA ) and 2, 2′-(1, 4-phenylene-bis(ethyne-2, 1-diyl))bis( N, N -diethyl-4-nitroaniline) (PDNA ), built up from two p -nitroaniline " push–pull " nonlinear optical (NLO) chromophores slightly conjugated through a 1, 4-phenylenebis(ethyne-2, 1-diyl) bridge have been synthesized and fully characterized. The crystal structure ofPNA reveals that the ground (off) state conformation corresponds to the centrosymmetric anti-conformer in which the molecular hyperpolarizability ( β ) is equal to zero. A computational investigation reveals that, once submitted to an intense electric field ( E ), the two p -nitroaniline subunits are gradually aligned in the direction of the field with the appearance of a metastable (on) state ( β ≠ 0, when E = 0), stabilized by conjugation. A loop of hysteresis is observed during the on ⇋ off cycles leading to a form of molecular bistability. The NLO response ofPNA has been investigated at different field intensities by the electric-field induced second-harmonic (EFISH) technique to provide experimental evidence for this behavior.